PENGGUNAAN STATISTIKA DESKRIPTIF UNTUK MELIHAT DISTRIBUSI POLA DATA YANG DITELITI: STUDI KASUS PROFIL PENGGUNA/PENGUNJUNG PERPUSTAKAAN TEKNOLOGI DI BIDANG JASA INFORMASI TEKNOLOGI PDII-LIPI - Rachmini Saparita (BACA: Jurnal Dokumentasi dan Informasi, 2025)
This paper discusses the use of descriptive statistics method in analyzing, interpreting and reporting of studied data pattern distributions. The paper also explains the advantages and isadvantages of using the method. User profile ofTechnology Library in Bajit PDII LIPI as a case study, show us a simple way of using descriptive statistics.